2000
DOI: 10.1097/00124645-200005000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Belonging and New Graduate Job Satisfaction

Abstract: This study investigated the relationship between sense of belonging and job satisfaction in the new graduate RN. Ninety-five new graduate RNs answered a survey about demographic information and work setting, as well as their satisfaction and sense of belonging in the work environment. McCloskey-Mueller's Satisfaction Scale and a modified version of the Hagerty-Patusky Sense of Belonging Instrument were used. The conceptual framework was derived from Marlene Kramer's work on Reality Shock (1974). Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(84 citation statements)
references
References 11 publications
5
76
0
3
Order By: Relevance
“…As detailed previously, Sherman (2013) stated a sense of belongingness is vital so nurses may have a support system. The results of this study support their finding as well the findings of McDaniel and Winter-Collins (2000) which argue that there is a significant relationship between sense of belonging and job satisfaction. Stechmiller and Yarandi (1992) also found that sense of belonging with valued and meaningful involvement would lead to higher job satisfaction.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…As detailed previously, Sherman (2013) stated a sense of belongingness is vital so nurses may have a support system. The results of this study support their finding as well the findings of McDaniel and Winter-Collins (2000) which argue that there is a significant relationship between sense of belonging and job satisfaction. Stechmiller and Yarandi (1992) also found that sense of belonging with valued and meaningful involvement would lead to higher job satisfaction.…”
Section: Resultssupporting
confidence: 89%
“…Winter- Collins & McDaniel (2000) studied the relationship between sense of belonging and job satisfaction in a sample of novice nurses. They found a significant relationship between sense of belonging and job satisfaction.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interviews with GAs' supervisors indicated they felt professional development helped make the GAs more marketable upon graduation. 2 The nursing literature [23][24][25][26][27] shows that professional development for new nurses increases job satisfaction and retention; however, not all nurses were aware of professional development opportunities.…”
Section: Professional Developmentmentioning
confidence: 99%
“…Among new nurses job satisfaction was positively related to a sense of belonging (Winter-Collins & McDaniel, 2000), and it was negatively related to conflict (Gardner, 1992), role ambiguity and role stress (Chang & Hancock, 2003). Additionally, achievement, advancement, the work itself, working conditions, status, supervision and security loaded onto the same factor as job satisfaction suggesting these were related to satisfaction (Munro, 1983).…”
Section: Outcomes Of the Transition Experiencementioning
confidence: 99%